Production of renewable fuels and chemicals by combining hydrothermal pretreatment with thermochemical conversion of woody biomass towards solid waste management (Indian Journal of Chemical Technology (IJCT), 2025)
Finding an ecologically and economically viable technique of processing biomass to produce biofuel is a vital one. Upgrading biomass for thermochemical processes using high temperature water (HTW) treatment is discussed in this study. In the present investigation, Ficus religiosa biomass is pretreated with HTW and pyrolyzed at temperature ranges from 350 °C to 550 °C. A fixed bed pyrolysis system is employed to convert raw biomass into valuable liquid and solid products. The liquid oil and char obtained through the pyrolysis process are characterized using different physical analysis. The chromatographic technique of gas chromatography mass spectroscopy (GC-MS) is also employed for the analysis of end products. The HTW treatment has been found to stimulate the synthesis of high energy value char and boost the product yield. The pretreatment is also more effective towards the production of aliphatic compounds.